Conceptual Modeling - ER 2007: 26th International Conference on Conceptual Modeling, Auckland, New Zealand, November 5-9, 2007, Proceedings - Parent, Christine (Springer, 2017)
This book constitutes the refereed proceedings of the 26th International Conference on Conceptual Modeling, ER 2007. Coverage in the papers includes data warehousing and data mining, design methodologies and tools, information and database integration, information modeling concepts and ontologies, integrity constraints, logical foundations of conceptual modeling, patterns and conceptual meta-modeling, semi-structured data and XML, as well as Web information systems and XML